2018
DOI: 10.1016/j.fsigen.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A GHEP-ISFG collaborative study on the genetic variation of 38 autosomal indels for human identification in different continental populations

Abstract: A collaborative effort was carried out by the Spanish and Portuguese Speaking Working Group of the International Society for Forensic Genetics (GHEP-ISFG) to promote knowledge exchange between associate laboratories interested in the implementation of indel-based methodologies and build allele frequency databases of 38 indels for forensic applications. These databases include populations from different countries that are relevant for identification and kinship investigations undertaken by the participating lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Thus far, iris color genotype-phenotype association results that we obtained for the population of Buenos Aires province are the only available data reported for Argentina, and they might be generalized to the entire country if we base our assertion on previous reports, which demonstrated genetic homogeneity throughout the country (García et al, 2019;Pereira et al, 2018). However, it will be necessary to confirm these results by performing a more comprehensive study of eye color genetics on samples from all over the country, since other authors reported a heterogeneous structure in the Argentinian population, proceeding from the extreme regions of the territory (Avena et al, 2012;Corach et al, 2010;Muzzio et al, 2018;Toscanini et al, 2011).…”
Section: P-valuementioning
confidence: 59%
“…Thus far, iris color genotype-phenotype association results that we obtained for the population of Buenos Aires province are the only available data reported for Argentina, and they might be generalized to the entire country if we base our assertion on previous reports, which demonstrated genetic homogeneity throughout the country (García et al, 2019;Pereira et al, 2018). However, it will be necessary to confirm these results by performing a more comprehensive study of eye color genetics on samples from all over the country, since other authors reported a heterogeneous structure in the Argentinian population, proceeding from the extreme regions of the territory (Avena et al, 2012;Corach et al, 2010;Muzzio et al, 2018;Toscanini et al, 2011).…”
Section: P-valuementioning
confidence: 59%
“…Unsurprisingly, not as many X chromosome INDEL marker systems have been described as compared to autosomal INDELs (e.g., Pereira et al, 2009;Freitas et al, 2010;Zaumsegel et al, 2013). In fact, no commercial kits being available, few systems have been subject to interlaboratorial comparisons, as in the case of autosomal INDELs, which stood international collaborative exercises (Pereira et al, 2018). One of the possible motifs for the lack of commercial kits is possibly due to the limited applications of X chromosome polymorphisms in forensic genetics when compared to autosomal markers.…”
Section: Current Developments: Numbers and Types Of X-chromosomal Marmentioning
confidence: 99%
“…Statistical parameters of forensic interest: PD (power of discrimination) and PE (power of exclusion), were computed using the Powerstats v1.2 spreadsheet [4]. These calculations were performed in 399 individuals from published articles [5,6].…”
Section: Autosomal Indelsmentioning
confidence: 99%